The role of PSMB9 upregulated by interferon signature in the pathophysiology of cutaneous lesions of dermatomyositis and systemic lupus erythematosus. (25th March 2016) - Nakamura, K.; Jinnin, M.; Kudo, H.; Inoue, K.; Nakayama, W.; Honda, N.; Kajihara, I.; Masuguchi, S.; Fukushima, S.; Ihn, H.
Summary: Background: Dermatomyositis (DM) and systemic lupus erythematosus (SLE) have common skin features, including dermal mucin deposition and interferon signature, although their roles are unknown. Objectives: To identify common or specific molecular changes in DM and SLE skin. Methods: Proteomic analysis was performed using DM and healthy skin. Glycosaminoglycans were analysed by high‐performance liquid chromatography. Results: The expression of 60 proteins was upregulated or downregulated in DM skin compared with healthy skin in the proteomic analysis. Among those proteins, PSMB9, an immunoproteasome subunit, was upregulated in the epidermis of DM and SLE, but not in other skin diseases. Furthermore, versican V1, a core protein for glycosaminoglycans, was upregulated, while type I collagen was downregulated in the dermis of DM and SLE skin. Interferon stimulated PSMB9 expression in cultured keratinocytes and reduced collagen expression in dermal fibroblasts, but did not affect versican expression. The PSMB9 knock‐down in keratinocytes led to significant suppression of transforming growth factor (TGF)‐β2 and TGF‐β3, inducers of versican synthesis. TGF‐β3 expression was upregulated in both DM and SLE, while TGF‐β2 expression was increased only in the DM epidermis. ΔDiHS‐diS1, a component of heparan sulfate, was significantly increased only in DM. TGF‐β2 expression significantly increased the ΔDiHS‐diS1 expression in dermal fibroblasts in vitro . Conclusions: The interferon signature in DM and SLE skin reduces collagen in dermal fibroblasts, whereas overexpression of PSMB9 induced by interferon stimulates versican inducers in epidermal keratinocytes. In addition, the TGF‐β2–ΔDiHS‐diS1 pathway may be responsible for the specific molecular change in DM skin. Abstract : What's already known about this topic? Dermatomyositis (DM) and systemic lupus erythematosus (SLE) have common skin features, including dermal mucin deposition and interferon signature. What does this study add? PSMB9 and versican V1, a core protein for glycosaminoglycan, were upregulated, while type I collagen was downregulated in both DM and SLE skin. The interferon signature reduces collagen in dermal fibroblasts of DM and SLE skin, while interferon‐induced PSMB9 overexpression induces transforming growth factor (TGF)‐β2/β3 in epidermal keratinocytes, which results in versican overexpression in dermal fibroblasts. The TGF‐β2–ΔDiHS‐diS1 pathway is responsible for the specific molecular changes to DM skin. What is the translational message? PSMB9 in the skin of patients with dermatomyositis and systemic lupus erythematosus has great potential as a diagnostic and therapeutic tool.